ANALISIS STRATEGI PENGEMBANGAN SEKTOR PERTANIAN DI KECAMATAN SUMBAWA (Pendekatan Analisis SWOT) - A Asmini; Roos Nana Sucihati; Nanda Maharaya (Jurnal Ekonomi & Bisnis, 2021)
This study aims to determine the strategy of developing the agricultural sector in Sumbawa District.The type of this study was descriptive qualitative. The data used in this study was primary data. The techniques used to collect data were through interviews and direct observation (documentation). The data analysis technique used in this study was SWOT analysis. The results of the study showed that according to the business field, the categories of agriculture, forestry and fisheries contributed to the economy in Sumbawa District,with the largest percentage distribution.Therefore, the agricultural sector could be a potential sector in Sumbawa District.The development strategy for corn commodity could be done through optimizing the government support, used good quality of corn seeds, optimizing corn farming management, improvement of trade system and corn production facilities.While the development strategy for rice commodities could be done through optimally utilize government support for rice farming, increasing the role of BPP in technology for rice farming, improved farm management for the farmer, improve post-harvest management, build infiltration wells for the farmer, improve supporting infrastructure conditions.